Anthracycline, taxane, and trastuzumab-based neoadjuvant chemotherapy in HER2-positive early breast cancer: phase II trial. Issue 1 (February 2023) - Conte, Benedetta; Montemurro, Filippo; Levaggi, Alessia; Blondeaux, Eva; Molinelli, Chiara; Cardinali, Barbara; Poggio, Francesca; Buzzatti, Giulia; Bighin, Claudia; Lambertini, Matteo; Del Mastro, Lucia
Objective: Neoadjuvant chemotherapy has become the preferred treatment in HER2-positive early breast cancer. Several trials investigated the neoadjuvant efficacy of dual HER2 blockade with anthracycline-free chemotherapy, whereas few data are available on single-agent trastuzumab and anthracycline-based regimens, which represent the standard of care in the adjuvant setting. This phase II, single-arm trial assessed anthracycline-based chemotherapy and trastuzumab as neoadjuvant treatment for high-risk HER2-positive breast cancer. Methods: Forty-three patients with stage II–III HER2-positive breast cancer were treated with 4 courses of neoadjuvant 5-fluorouracil 600 mg/m 2, epirubicin 90 mg/m 2, cyclophosphamide 600 mg/m 2 (FEC ×4) every 21 days, followed by 12 courses of weekly paclitaxel 80 mg/m 2 and trastuzumab 2 mg/Kg IV (loading dose 4 mg/kg). Results: Pathologic complete response (pCR) was observed in 22 (51%) of 43 patients. After a median follow-up of 6 years, the 5-year disease-free survival and overall survival were 85.8% (95% confidence interval 75.9%–97%) and 89.6% (80.4%–99.8%), respectively. A temporary decrease in left ventricular ejection fraction was observed in two patients. No cardiac death or congestive heart failure occurred. One patient died due to febrile neutropenia. Conclusions: FEC ×4 followed by paclitaxel and trastuzumab was associated with high pCR rates and favorable long-term outcomes. However, this regimen was associated with relevant hematologic toxicity.